Polar Stars. Why the Political Ideologies of Modernity still Matter - Barisione, Mauro (Milano University Press, 2021)
Against the cliché that ours is a post-ideological age, the thesis of this book is that political ideologies are part of the very logic of modernity and continue to permeate 'hypermodern' politics. Using a multitude of primary sources (texts) and data, the author identifies the 'polar stars' - guiding principles such as order, freedom and equality - around which ideological camps, mainly in Europe, have developed in recent centuries. As an alternative to the overly reductive concepts of "left" and "right", this book adopts a different strategy to analyse the orientations of contemporary political movements, parties, policies and voters: it reconstructs the main ideological "matrices" of modern politics in their historical origins and in the subsequent phases of radicalisation and hybridisation, which still continue, both between these political matrices and with "metapolitical" ideologies such as populism. Moreover, the book outlines a broader theory that helps to interpret recent ideological trends as reflecting a peculiar "double movement" of modernity: the continuous tension between liberalizing pressures for more individual rights and, conversely, "centripetal" countermovements along both the matrix of order and that of socioeconomic equality.